Development of an expected model for the protection of Copyright of software code using digital watermarking - Rastogi, H; Sharma, BK (International Journal of Computer Sciences and Engineering, 2025)
The research done in this paper aimed to develop a model for the protection of copyright of software using Digital Watermarking by providing a proper way for designing the software. Digital watermarking has now become the research area for the protection of intellectual property right. In this research paper, the technique of cryptography with a assigned key is implemented for the development of the model. This paper gives the procedure of the implementation of the technique.